The solution route synthesis of the Cu0.5Ag1.5InSe3 compound for thermoelectric applications - Chansaenpak K. (2014)
Cu0.5Ag1.5InSe3 compound which is used as a thermoelectric material was successfully synthesized by a simple solution route. The metal ions were reduced simultaneously under alkaline conditions by NaBH4. The types of solvent, reaction temperature, indium precursors, and reaction time were studied as the parameters of the synthesis method. The prepared powders were investigated by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDS). The results show that the reaction temperature is the main factor affecting Cu0.5Ag1.5InSe3 formation. Finally, suitable conditions to prepare Cu0.5Ag1.5InSe3 particles were ethylene glycol as a solvent, 200 degree Celsius as a reaction temperature, indium nitrate as an indium precursor, and 72 h as a reaction time.